2016
DOI: 10.1080/08927014.2016.1233325
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of adhesive-related genes in the freshwater cnidarianHydra magnipapillataby transcriptomics and proteomics

Abstract: The differentiated ectodermal basal disc cells of the freshwater cnidarian Hydra secrete proteinaceous glue to temporarily attach themselves to underwater surfaces. Using transcriptome sequencing and a basal disc-specific RNA-seq combined with in situ hybridisation a highly specific set of candidate adhesive genes was identified. A de novo transcriptome assembly of 55,849 transcripts (>200 bp) was generated using paired-end and single reads from Illumina libraries constructed from different polyp conditions. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 80 publications
5
53
0
Order By: Relevance
“…Further supporting an increased occurrence of genomic heterogeneity among LL/LG colonies, we found increased frequencies of genes in LL/LG genomes that may facilitate nonclonal colony formation: (a) NeuB that synthesizes sialic acids, which are a component of cyanobacterial extracellular polymeric substances (Strom, Bright, Fredrickson, & Brahamsha, ; Zippel & Neu, ) and play important roles in cellular recognition and adhesion (Gunawan et al, ); (b) sialidases that may facilitate cellular adhesion by uncovering carbohydrate receptors that are recognized by bacterial adhesins (Vimr, ); (c) pfam06229 (FRG1‐like domain) that contains a Hydra spp. gene linked to this freshwater cnidarian's ability to adhere to underwater surfaces (Rodrigues et al, ); and (d) a bacterial adhesin (pfam03865: haemolysin secretion/activation protein ShlB/FhaC/HecB) (Moslavac et al, ) that facilitates adhesion to other cells in pathogenic and symbiotic interactions (Hooper & Gordon, ). Genes regulating cell recognition and adhesion should be less important for clonal colonies, where daughter cells remain attached after binary fission (Kessel & Eloff, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further supporting an increased occurrence of genomic heterogeneity among LL/LG colonies, we found increased frequencies of genes in LL/LG genomes that may facilitate nonclonal colony formation: (a) NeuB that synthesizes sialic acids, which are a component of cyanobacterial extracellular polymeric substances (Strom, Bright, Fredrickson, & Brahamsha, ; Zippel & Neu, ) and play important roles in cellular recognition and adhesion (Gunawan et al, ); (b) sialidases that may facilitate cellular adhesion by uncovering carbohydrate receptors that are recognized by bacterial adhesins (Vimr, ); (c) pfam06229 (FRG1‐like domain) that contains a Hydra spp. gene linked to this freshwater cnidarian's ability to adhere to underwater surfaces (Rodrigues et al, ); and (d) a bacterial adhesin (pfam03865: haemolysin secretion/activation protein ShlB/FhaC/HecB) (Moslavac et al, ) that facilitates adhesion to other cells in pathogenic and symbiotic interactions (Hooper & Gordon, ). Genes regulating cell recognition and adhesion should be less important for clonal colonies, where daughter cells remain attached after binary fission (Kessel & Eloff, ).…”
Section: Discussionmentioning
confidence: 99%
“…(c) pfam06229 (FRG1-like domain) that contains a Hydra spp. gene linked to this freshwater cnidarian's ability to adhere to underwater surfaces (Rodrigues et al, 2016); and (d) a bacterial adhesin (pfam03865: haemolysin secretion/activation protein ShlB/FhaC/ HecB) (Moslavac et al, 2005) that facilitates adhesion to other cells in pathogenic and symbiotic interactions (Hooper & Gordon, 2001). Genes regulating cell recognition and adhesion should be less important for clonal colonies, where daughter cells remain attached after binary fission (Kessel & Eloff, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…C-lectin domains have been shown to serve as interfacial linkers, joining soft tissues to the byssus of the fan shell Atrina pectinata (Yoo et al 2016). Galactose-binding lectin domains have been detected in sea star and sea urchin adhesive proteins (Hennebert et al 2014; Lebesgue et al 2016), as well as proteins from the adhesive disk of the freshwater cnidarian Hydra (Rodrigues et al 2016). These proteins may be discoidin-like (Hennebert et al 2015; Lebesgue et al 2016), as was found for one of the H-lectins in slug glue.…”
Section: Discussionmentioning
confidence: 99%
“…translocation of the foot from one place to another. This is initiated by 'foot detachment' where the basal disk detaches from a substrate's surface (Rodrigues, Ostermann et al 2016). Here we tested how these two common behaviors of Hydra are affected by various physiological and environmental conditions.…”
Section: Hydra's Contractile Behavior Affected By Media Osmolaritymentioning
confidence: 99%